Preparation and Characterization of Fenofibrate-Loaded PVP Electrospun Microfibrous Sheets - Emese Sipos; Tamás Csatári; Adrienn Kazsoki; Attila Gergely; Enikő Bitay; Zoltán-István Szabó; Romána Zelkó (MDPI AG, 2020)
Fenofibrate-loaded electrospun microfibrous sheets were prepared in an attempt to enhance the dissolution of the poorly soluble antihyperlipidemic agent and to improve its bioavailability. Physicochemical changes that appeared during the electrospinning process were monitored using a wide array of solid-state characterization techniques, including attenuated total reflectance Fourier-transformed infrared spectroscopy and positron annihilation lifetime spectroscopy, while fiber morphology was monitored via scanning electron microscopy. Dissolution studies carried out both in 0.025 M sodium dodecyl sulfate and in water revealed an immediate release of the active agent, with an approximately 40-fold release rate enhancement in water when compared to the micronized active agent. The dramatic increase in dissolution was attributed partially to the amorphous form of the originally crystalline active agent and the rapid disintegration of the electrospun microfibrous sheet due to its high surface area and porosity. The obtained results could pave the way for a formulation of the frequently used antihyperlipidemic agent with increased bioavailability.